Early Thrombectomy Protects the Internal Capsule in Patients With Proximal Middle Cerebral Artery Occlusion. Issue 5 (8th April 2021) - Kaesmacher, Johannes; Kaesmacher, Mirjam; Berndt, Maria; Maegerlein, Christian; Mönch, Sebastian; Wunderlich, Silke; Meinel, Thomas R.; Fischer, Urs; Zimmer, Claus; Boeckh-Behrens, Tobias; Kleine, Justus F.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Proximal middle cerebral artery (MCA) occlusions impede blood flow to the noncollateralized lenticulostriate artery territory. Previous work has shown that this almost inevitably leads to infarction of the dependent gray matter territories in the striate even if perfusion is restored by mechanical thrombectomy. Purpose of this analysis was to evaluate potential sparing of neighboring fiber tracts, ie, the internal capsule. Methods: An observational single-center study of patients with proximal MCA occlusions treated with mechanical thrombectomy and receiving postinterventional high-resolution diffusion-weighted imaging was conducted. Patients were classified according to internal capsule ischemia (IC+ versus IC−) at the postero-superior level of the MCA lenticulostriate artery territory (corticospinal tract correlate). Associations of IC+ versus IC− with baseline variables as well as its clinical impact were evaluated using multivariable logistic or linear regression analyses adjusting for potential confounders. Results: Of 92 included patients with proximal MCA territory infarctions, 45 (48.9%) had an IC+ pattern. Longer time from symptom-onset to groin-puncture (adjusted odds ratio, 2.12 [95% CI, 1.19–3.76] per hour), female sex and more severe strokes were associated with IC+. Patients with IC+ had lower rates of substantial neurological improvement and functional independence (adjusted odds ratio, 0.26 [95% CI, 0.09–0.81] and adjusted odds ratio, 0.25 [95% CI, 0.07–0.86]) after adjustment for confounders. These associations remained unchanged when confining analyses to patients without ischemia in the corona radiata or the motor cortex and here, IC+ was associated with higher National Institutes of Health Stroke Scale motor item scores (β, +2.8 [95% CI, 1.5 to 4.1]) without a significant increase in nonmotor items (β, +0.8 [95% CI, −0.2 to 1.9). Conclusions: Rapid mechanical thrombectomy with successful reperfusion of the lenticulostriate arteries often protects the internal capsule from subsequent ischemia despite early basal ganglia damage. Salvage of this eloquent white matter tract within the MCA lenticulostriate artery territory seems strongly time-dependent, which has clinical and pathophysiological implications.